Sleep quality among School of Medicine students of a Peruvian university during the return to in-person classes after the COVID-19 social restrictions - Martin-Osorio, Andrea Magaly (2024)
Objective: To evaluate the sociodemographic and academic characteristics associated with sleep quality among School of Human Medicine students. Materials and methods: A cross-sectional study was carried out in a randomly selected sample of 184 School of Human Medicine students from a private university located in the city of Lima, Peru. The study was conducted between June and July 2022, a period of gradual return to in-person classes. The participants completed an anonymous virtual survey containing questions on sociodemographic and academic factors as well as the Pittsburgh Sleep Quality Index (PSQI). This instrument comprised seven parameters with scores ranging from 0 to 21, where a good sleep quality was established from 0 to 5 points. The outcome was dichotomous (good and poor sleep quality), so binary logistic regression was used to evaluate the associated factors. Results: Females accounted for 53.26 % and the mean age was 20.05 with a standard deviation of 1.73. Concerning the hours of class time, 61.35 % were taught online. As for the sample, the prevalence of poor sleep quality was 69.02 %, out of which 76.53 % were females and 60.47 % males. The mean percentage of online classes was higher among those with poor sleep quality compared to those with good sleep quality (63.48 % versus 56.58 %, p = 0.030). Regardless of the percentage of online classes, females were twice as likely to have poor sleep quality (OR = 2.00, 95 % CI: 1.05 to 3.82). Conclusions: Poor sleep quality affected 7 out of 10 School of Human Medicine students in the context of the gradual return to in-person classes after the COVID-19 social restrictions. Females had a higher chance of poor sleep quality, regardless of the percentage of online classes.